Looking for the right blend: a blended EFL university writing course - Chen, Ping-Ju (Computer assisted language learning, 2023)
As a primary form of communication in the global village, the importance of English writing cannot be emphasized enough. Most academic institutions regard training their students to write English effectively as a goal of the curriculum. Here in Taiwan is no exception to that; therefore, more and more colleges start to offer English writing courses for their students. To develop a suitable EFL college writing course for English majors, a blended course that integrates traditional classroom activities and technology was proposed by the author based on the data analysis from a pilot study and literature review. This one-year writing course was then implemented and researched employing pre-and post-writing tests, perceptions questionnaire, interview, and class observation. This article reports the effectiveness of the course from three dimensions: the students' linguistic performance, their perceptions of the course, and the most essential elements that made the course effective. The results show that after the course of study, the students could write longer and more grammatically complex texts. Overall, they felt positive about the course, regarding the instructor as facilitative and blogging to write as beneficial in guiding them to write. According to the quantitative and qualitative findings, the most essential elements of a blended EFL university writing course by rank are (1) instructor's guidance/scaffolding, (2) a variety of writing practices including free writing, (3) blogging to writing, (4) introduction of writing-related online resources, (5) good lesson planning and classroom activities, and (6) a conducive learning community. One thing needs our attention is that the digital natives like the subjects of the present study still need a teacher interacting with them in real time when learning to write and the guidance is suggested to be conducted in a brick-and-mortar classroom, which cannot be replaced by other technologies.